Pemberdayaan Masyarakat di Bidang Pertanian melalui Pembuatan Pupuk Organik - Zamzul Hamid (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Organic fertilizer is defined as fertilizer that is partly or wholly derived from plants and/or animals that has gone through an engineering process, can be in solid or liquid form which is used to supply organic material to improve the physical, chemical and biological properties of the soil. The aim of this activity is to empower the community through making organic fertilizer in the agricultural sector. The activity steps include: 1) Preparation stage. The preparation stage is very important as a form of more mature planning to achieve better things. This preparation stage includes observations and interviews with partners and the community, checking the implementation location, in this case I used Sumbek Hamlet, Wajageseng Village, Kopang District, Central Lombok Regency, establishing collaboration with youth and the entire community, preparing tools and materials for the main program which includes everything needed in this training; and 2) Program implementation stage. The program implementation stages are described as follows: the process of collecting cow dung which is processed into fertilizer, the process of mixing cow dung with straw, and the fermentation process for up to ± 30 days to make it into soil to be used as fertilizer. The results achieved in this training activity were the acquisition of knowledge by the community and youth about how to make organic fertilizer using existing materials. The community is able to minimize expenditure on purchasing fertilizer and reduce the use of chemical fertilizers. Through this activity, the public also understands more about the negative impacts caused by the use of chemical or inorganic fertilizers if used over a long period of time. This community empowerment can also support various village activities in organizing training in the agricultural sector, because the community is able to create their own fertilizer from materials that are easily obtained.